2016
DOI: 10.1530/eje-15-0986
|View full text |Cite
|
Sign up to set email alerts
|

suPAR level is associated with myocardial impairment assessed with advanced echocardiography in patients with type 1 diabetes with normal ejection fraction and without known heart disease or end-stage renal disease

Abstract: Aim Heart disease is a common fatal diabetes-related complication. Early detection of patients at particular risk of heart disease is of prime importance. Soluble urokinase plasminogen activator receptor (suPAR) is a novel biomarker for development of cardiovascular disease. We investigate if suPAR is associated with early myocardial impairment assessed with advanced echocardiographic methods. Methods In an observational study on 318 patients with type 1 diabetes without known heart disease and with normal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
3
25
2
Order By: Relevance
“…By demonstrating that suPAR is predictive of impaired myocardial relaxation, an early manifestation diastolic dysfunction commonly associated with ageing, our current study builds on this emerging link between suPAR and diastolic function, particularly as assessed by echocardiography. Diabetes mellitus was not a significant predictor of myocardial function in our study, in contrast to Theilade et al’s study [ 12 ] that was prespecified to study suPAR among diabetic patients. Further, we had acquired echocardiographic images simultaneously with blood sampling at the same study visit, possibly eliminating potential clinical events intervening between assessment of myocardial function and blood sampling that may inaccurately depict the relationship between suPAR and myocardial function.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…By demonstrating that suPAR is predictive of impaired myocardial relaxation, an early manifestation diastolic dysfunction commonly associated with ageing, our current study builds on this emerging link between suPAR and diastolic function, particularly as assessed by echocardiography. Diabetes mellitus was not a significant predictor of myocardial function in our study, in contrast to Theilade et al’s study [ 12 ] that was prespecified to study suPAR among diabetic patients. Further, we had acquired echocardiographic images simultaneously with blood sampling at the same study visit, possibly eliminating potential clinical events intervening between assessment of myocardial function and blood sampling that may inaccurately depict the relationship between suPAR and myocardial function.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, we had acquired echocardiographic images simultaneously with blood sampling at the same study visit, possibly eliminating potential clinical events intervening between assessment of myocardial function and blood sampling that may inaccurately depict the relationship between suPAR and myocardial function. In contrast to Theilade’s study [ 12 ] that had a median interval of 116 days between echocardiography acquisition and blood sampling, the observed value of suPAR in predicting myocardial function in our study is unlikely influenced by other unknown systemic disease processes. This is especially pertinent in studies that evaluate suPAR as a potential biomarker of disease, because suPAR may represent general states of ill-health.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Considering that impaired renal function and the presence of microalbuminuria substantially enhance the risk of cardiovascular disorders [11] , [12] , it is thought that suPAR may represent a novel biomarker for various cardiovascular disorders. In fact, suPAR levels may be elevated in patients with coronary artery disease, stroke, and heart failure [13] , [14] , [15] , [16] . We recently reported that suPAR is associated with a low left ventricular ejection fraction (LVEF) and increased plasma levels of brain-type natriuretic peptide (BNP) [17] .…”
Section: Introductionmentioning
confidence: 99%